Computed tomography of the anteverted internal auditory canal. - Silver, A J; Jahn, A F; Sane, P; Mawad, M E; Ganti, S R; Hilal, S K (American Journal of Neuroradiology, 1983)
A symmetric variation in the course of the internal auditory canals, visualized best on axial computed tomographic views with thin sections, was observed in three of 75 patients examined mainly for hearing, vestibular, and facial nerve dysfunction. The incidence may be lower in an unselected population. In coronal section, with either pluridirectional or computed tomography, an anteverted internal auditory canal may mimic the normal configuration of "medial narrowing" because of the effect of partial sectioning of an angled cylinder with a thin beam. The pathologic significance of this finding is uncertain. In the three cases reported, it was associated with adult-onset uni- or bilateral hearing loss. Vestibular function may be compromised but may not be symptomatic. Facial nerve function was not impaired.